Synthesis, Characterization and Biological Evaluation of Esters Derived from Sulfamethoxazole Drug - Inas S. Mahdi (Journal of Global Pharma Technology, 2016)
A series of novel esters compounds have been prepared from the reaction of sulfamethoxazole drug with α-chloro acetyl chloride then reaction of the resulting compound with various carboxylic acids and carboxylic drugs. The modern ester has been diagnosed by 1HNMR, FTIR spectral data and their physical properties and some of them were screened for their antibacterial activity.Keywords: Sulfamethoxazole, Esters, Antibacterial activity.